PERSEPSI MAHASISWA TERHADAP KULIAH ONLINE PADA MASA PANDEMI COVID-19 - Rayyan Sugangga; Iradah Rahman (Jurnal Akademika, 2021)
The Corona Outbreak requires that all lecture activities be carried out online. This sudden and massive change cannot immediately proceed smoothly. Adaptation is needed from institutions, lecturers and students. The purpose of this study was to determine student perceptions of lectures conducted online. The research method used was qualitative with a survey study approach. The results of this study illustrate that not all students can follow the course of online lectures. The research also explained the best practices that need to be considered in order to optimize online lectures. Keywords: online lectures, student perceptions, surveys, online learning